Peaceful coexistence in the city of Diwaniyah Sabean Mandaeans as an example (Journal of the College of Basic Education, 2022)
This study seeks to clarify two important aspects, the first: to give an overview of the Mandaean Sabeans, the history of their presence in the land of Iraq and the city of Diwaniyah, and their monotheistic religion that strikes in the depths of the land of Mesopotamia, and their preservation of their ancient beliefs and rituals. They are the largest Sabean sect present in Iraq. On this one hand, and on the other hand, this study seeks to shed light on the peaceful coexistence in the city of Diwaniyah, and how they merged with its Muslim-majority society, accepted and accepted it, and they were part of the fabric of a cohesive society, they practiced their rituals freely, In doing so, they were not subjected to any harassment, as they are an important part of the city.